Modeling the interplay of EFL learners' basic psychological needs, grit and L2 achievement - Elahi Shirvan, Majid; Alamer, Abdullah (Journal of multilingual and multicultural development, 2024)
Given the recent attention to language-domain-specific grit in the field of SLA and the scarcity of research on the antecedents of L2 grit, we proposed a model that links L2 learners' basic psychological needs (BPN) (i.e. autonomy, competence, and relatedness), L2 grit (i.e. perseverance of effort (PE) and consistency of interest (CI)), and L2 achievement (measured by students' scores on English courses). L2 Saudi undergraduate students who study English were invited to participate. The findings indicated that except for the path from competence to achievement and from CI to achievement, all direct paths in the model were significant. More specifically, only PE, but not CI, was positively associated with L2 achievement. Also, all constructs of BPN have a positive influence on PE, but only autonomy has a positive link with CI. The findings illustrated plausible antecedents of L2 grit and showed pathways in which L2 grit operated as mediators in the association between BPN and L2 achievement. Using partial least squares structural equation modelling (PLS-SEM) to examine the mediational model allowed us to predict unseen scores on the outcome; thus, providing support for the out-of-sample predictive power (predictive validity) of our structural model.